Non-linear Phased Array Imaging of Flaws Using a Dual and Tri Frequency Modulation Technique - Malfense Fierro, Gian Piero; Meo, Michele (Frontiers in Built Environment, 2020)
Recently, there has been high interest in the capabilities of non-linear ultrasound techniques for damage/defect detection as these techniques have been shown to be more sensitive than linear ultrasound techniques for certain types of damage. This paper presents a non-linear ultrasound phased array modulation method based on the principles of frequency and amplitude modulation, for the detection and imaging of material defects/damage. The proposed method requires the use of standard ultrasound phased array systems, which use multiple transmitting and receiving elements. An adjusted dual frequency method and tri-frequency is employed, which focuses on the evaluation of harmonic sidebands. A pump signal at a frequency of f2 is used to initialize a “breathing/ringing” crack scenario after which a second frequency at f1 is used to further excite the crack and improve the probability that harmonic sidebands are generated. The modulation method employs a subtraction method which is used to filter out the fundamental frequencies. The technique adds benefits in ensuring that equipment based non-linearities produced by single frequency setups are eliminated, ensuring that only defect related non-linearities are present. A closed fatigue crack was evaluated using multiple linear and non-linear ultrasound phased array techniques with the suggested method showing clear benefits. Furthermore, it is shown that modulation techniques with more than two driving frequencies could further improve damage detection capabilities of phased array systems.